L’art moderne en Colombie. - Elsa Crousier (IdeAs)
Through a discussion of the essays by the art critic Marta Traba (1923-1983), this article offers a brief overview of the processes by which modern art was developed and defined in Colombia during the twentieth century. Modernity in Colombian art grew out of the influence of European and North American models, before assuming a stance that opposed a concept of modern art deemed overly occidentalist and internationalist. The criticism of Marta Traba, which has considerably shaped the reception of modern art in Colombia, accounts for these two tendencies, across the divide between the assimilation of foreign models and the advancement of a strictly Latin American aesthetic modernity.